Utilization of pain rating scales in pediatric care among health professionals in a children's hospital in Kenya - Godfrey Mbaabu Limungi; Drusilla Makworo; Sherry Oluchina; Patrick M. Mburugu (Elsevier, 2021)
Background: Pain is the most common stimuli experienced by paediatric patients. It is mainly managed based on intensity, determined through utilization of pain rating scales. Utilization of pain measurement tools in paediatric care is vital as they indicate the level and intensity of pain in the patients. Purpose of the study: The study assessed utilization of pain rating scales in a children's hospital as a basis for making recommendation for their adoption by the Ministry of Health, Kenya. Methodology: This was a descriptive cross-sectional study utilizing both quantitative and qualitative approaches. It was conducted in a children's hospital in Nairobi-Kenya. The study population comprised of health professionals working at the hospital and patients medical records. Data was collected using semi- structured self-administered questionnaire, key informant interview guide (KII) and observation check list from a sample size of 158 Health Professionals, five key informants and 70 patients' documents. Quantitative data was analysed using descriptive statistics whereby data was summarized using frequency tables and presented using pie chart, and bar graphs. A content analysis was performed on qualitative data based on stages of qualitative data analysis. Results: The study revealed that the hospital has adopted four pain rating scales which included Neonatal Guide Score, FLACC, Wong Baker faces scale, and Numerical pain scale. These tools were excellently being utilized by the Health Professionals at the hospital. Prior training of the staff on pain assessment, availability of pain management protocols and frequent auditing of the utilization of pain rating scales facilitated the utilization. Being newly employed and use of FLACC in mentally challenged patients were the main challenges in utilization of pain rating scales at the hospital. Conclusion: Health system factors play a major role in excellent utilization of pain rating scales at the children's hospital. Staff training, protocols on pain management and frequent auditing improved utilization of pain measurement tools. Inclusion of pain assessment in the curriculum for all institutions training health professionals would address the challenge posed by the newly employed health professionals in utilization of pain rating scales. Further research on validity of FLACC in cognitively challenged children may be necessary in this setting.